FC 061OSTEOPONTIN AND ITS ASSOCIATION WITH ADVERSE EVENTS IN THE GERMAN CHRONIC KIDNEY DISEASE STUDY. (29th May 2021) - Steinbrenner, Inga; Cheng, Yurong; Nadal, Jennifer; Schmid, Matthias; Kotsis, Fruzsina Kinga; Meiselbach, Heike; Schneider, Markus; Krane, Vera; Nauck, Matthias; Eckardt, Kai-Uwe; Köttgen, Anna; Sekula, Peggy; et al.
Abstract: Background and Aims: Osteopontin (OPN) is synthesized in the thick ascending limb of Henle's loop and in the distal tubule. Numerous studies have shown that OPN mRNA and protein expression is increased in animal models of many different renal diseases, especially glomerular diseases as well as diabetic nephropathy. Here, high OPN expression correlated with proteinuria, reduction of creatinine clearance, fibrosis as well as macrophage and T-cell infiltration. OPN has therefore been suggested to be a promising biomarker for various kidney diseases. Further studies are needed to fully understand its role in kidney (patho-)physiology and its potential as a marker of kidney disease progression and adverse renal events. We therefore evaluated the association of OPN with kidney events and all-cause mortality in a cohort of CKD patients, the German Chronic Kidney Disease (GCKD) study. Method: OPN was measured from baseline serum samples using the Quantikine Human OPN Immunoassay. Coefficients of variation were <7%. Kidney events included kidney failure treated with kidney replacement therapy (dialysis, transplantation), and death due to discontinuation of dialysis treatment. Another event of interest was all-cause mortality. All events were abstracted from hospital discharge letters and death certificates by trained physicians based on a standardized endpoint catalogue. Cross-sectional regression models (dependent variables: eGFR, logUACR) adjusted for confounding variables (Table 1 legend ) were fitted. Multi-variable adjusted Cox proportional hazard regression analyses were conducted. Estimated risks are expressed as cause-specific hazard ratios (HR) for all-cause mortality and kidney events, with death of other causes as the competing event. Sensitivity analyses included evaluation of all models stratified by the three most common causes of kidney disease in GCKD: hypertensive nephropathy, primary glomerular disease, and diabetic nephropathy. Results: Over 6.5 years of follow-up, 473 kidney events and 582 deaths occurred among 4, 950 GCKD patients. Hundred-and-forty-eight deaths and 62 kidney events occurred in 1, 143 hypertensive nephropathy patients, 49 deaths and 118 kidney events occurred in 935 primary glomerular nephropathy patients, and 170 deaths and 99 kidney events in diabetic nephropathy patients (Table 1). Overall mean age was 60.1 years (±12.0), with 60.3% men. Median OPN levels were 29.2 ng/mL (IQR 21.2). Cross-sectionally a 10% change in OPN was associated with 0.5% lower eGFR on average (p<0.0001, 95% CI: -6.4 to -4.6) and a 7% change in UACR (p<0.0001, 95% CI: 0.6 to 0.8) overall. Stratified by leading cause of kidney disease, results for eGFR and UACR were of similar direction for all groups (Table 1 A). After adjusting for baseline eGFR and UACR (Table 1 B), higher OPN levels were associated with a higher risk of kidney events overall (HR 1.4, p<0.001, 95% CI 1.1-1.7). For patients with diabetic nephropathy this risk was even higher (HR 2.2, p<0.01, 95% CI 1.4-3.6). Higher OPN levels were also associated with higher risk of all-cause mortality overall (HR 1.5, p<0.0001, 95% CI 1.3-1.8) as well as for diabetic nephropathy patients (HR 1.7, p<0.01, 95% CI 1.2-2.4). HRs for the hypertensive nephropathy and primary glomerular nephropathy groups showed mostly the same effect directions, but did not reach significance after adjustment. Conclusion: Higher OPN levels were associated with lower eGFR and higher UACR cross-sectionally and significantly associated with a higher risk of renal events and all-cause mortality especially for diabetic nephropathy patients even after adjustment for baseline eGFR, UACR and other confounding factors. These results are supportive of OPN being a potential marker of CKD progression and mortality.